Spectroscopy Study of Honey Pineapple Peels Extracted in Different Solvents - Kurniawan, Yehezkiel Steven; Setiyono, Edi; Adhiwibawa, Marcelinus Alfasisurya Setya; Priyangga, Krisfian Tata Aneka; Yuliati, Leny (Ma Chung Research Center for Photosynthetic Pigments, 2021)
In the present work, we investigated the extract of honey pineapple peels in distilled water, ethanol, and acetone solvents. The spectroscopy study of each extract was performed using a Fourier transform infrared (FTIR) spectrometer, an ultraviolet-visible (UV-Vis) spectrophotometer, and a spectrofluorometer. The FTIR spectrum of the distilled water extract indicated that the distilled water extract may contain alcohol or carboxylic acid compounds. Meanwhile, the ethanolic extract may contain alcohol or carboxylic acid, or ether compounds. On the other hand, the acetone extract may contain alcohol or ether or aromatic or aliphatic compounds. The UV-Vis spectrum of the honey pineapple peels extracted in the distilled water, ethanol, and acetone showed a broad absorption signal at UV region (< 300 nm), four absorption signals at UV region (232-368 nm), and four absorption signals at UV region (231-368 nm) with a weak absorption signal at the visible region at 559 nm, respectively. The distilled water and acetone extracts gave fluorescence signals, however, the ethanolic extract showed no fluorescence intensity. From the FTIR, UV-Vis, and fluorescence spectra characterization, the extracted natural pigments from the honey pineapple peels in distilled water, ethanol, and acetone solvents were identified. The distilled water extract may contain polar flavonoid or steroid compounds while the ethanolic extract may contain polar carotenoid pigments. On the other hand, the acetone extract may contain carotenoid and chlorophyll pigments as shown by an emission signal at 670 nm.